2018
DOI: 10.1111/ijun.12174
|View full text |Cite
|
Sign up to set email alerts
|

The Lymphoedema Genitourinary Cancer Questionnaire in urology follow‐up clinics

Abstract: Is the Lymphoedema Genitourinary Cancer Questionnaire (LGUCQ) useful to men treated for genitourinary cancer through facilitating symptom disclosure? Lymphoedema can be debilitating and progressive and its association with bladder, prostate, testicular and penile cancer, either as a consequence of treatment or progressive disease is well recognized. However, lymphoedema is generally unrecognized during follow‐up. Research on genitourinary cancer‐related lymphoedema is sparse with a lack of reliable prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…PROMs were also a means to structure consultations and interactions, and aided to prioritise issues of importance [10,29,37,40,42,43,50,57] (see also "Attitudes to the care experience"). Some studies [31,42,48,49] noted that HPs also saw PROMs as prompting patients to identify and prioritise issues from their own perspectives: "Actually, it [using the questionnaire] meant that we talked about issues which we wouldn't otherwise have touched upon because she hadn't thought of it, and I usually don't ask about it / … / it…”
Section: Attitudes To Identifying Patient Issues and Needsmentioning
confidence: 99%
See 4 more Smart Citations
“…PROMs were also a means to structure consultations and interactions, and aided to prioritise issues of importance [10,29,37,40,42,43,50,57] (see also "Attitudes to the care experience"). Some studies [31,42,48,49] noted that HPs also saw PROMs as prompting patients to identify and prioritise issues from their own perspectives: "Actually, it [using the questionnaire] meant that we talked about issues which we wouldn't otherwise have touched upon because she hadn't thought of it, and I usually don't ask about it / … / it…”
Section: Attitudes To Identifying Patient Issues and Needsmentioning
confidence: 99%
“…Concerns Checklist "The aim of the study is to explore how specialist cancer nurses carry out first Items from PRO-CTCAE and PROMIS and authors own "Our primary objectives were the following: (1) solicit feedback from cancer clinicians and patients to develop a web- Sensitive issues A few studies (n = 6) reported that PROMs could "facilitate open dialogue and discussion of sensitive topics" [29] (p776), related to issues that could be potentially upsetting or distressing [33,40,43,48]. It was noted that this may vary by patient: "I do think it's an important issue for patients, but obviously for some people it's an embarrassing one to bring up … and it might be that you can't solve the problem … but for some patients it's a very simple 'how many platelets do I need to have sex?"…”
Section: Symptoms Andmentioning
confidence: 99%
See 3 more Smart Citations